Hypertension in children and adolescents: A consensus document from ESC Council on Hypertension, European Association of Preventive Cardiology, European Association of Cardiovascular Imaging, Association of Cardiovascular Nursing & Allied Professions, ESC Council for Cardiology Practice and Association for European Paediatric and Congenital Cardiology. (8th July 2022) - de Simone, Giovanni; Mancusi, Costantino; Hanssen, Henner; Genovesi, Simonetta; Lurbe, Empar; Parati, Gianfranco; Sendzikaite, Skaiste; Valerio, Giuliana; Di Bonito, Procolo; Di Salvo, Giovanni; Ferrini, Marc; Leeson, Paul; et al.
Graphical Abstract: Graphical abstract Suggested diagnostic algorithm, clinical work-up, and management of arterial hypertension in children and adolescents. Abstract: Definition and management of arterial hypertension in children and adolescents are uncertain, due to different positions of current guidelines. The European Society of Cardiology task-force, constituted by Associations and Councils with interest in arterial hypertension, has reviewed current literature and evidence, to produce a Consensus Document focused on aspects of hypertension in the age range of 6–16 years, including definition, methods of measurement of blood pressure, clinical evaluation, assessment of hypertension-mediated target organ damage, evaluation of possible vascular, renal and hormonal causes, assessment and management of concomitant risk factors with specific attention for obesity, and anti-hypertensive strategies, especially focused on life-style modifications. The Consensus Panel also suggests aspects that should be studied with high priority, including generation of multi-ethnic sex, age and height specific European normative tables, implementation of randomized clinical trials on different diagnostic and therapeutic aspects, and long-term cohort studies to link with adult cardiovascular risk. Finally, suggestions for the successful implementation of the contents of the present Consensus document are also given.